Catalytic Decomposition of CF4 by Mesoporous Aluminum Coupled with Non-Thermal Plasma - Fenghua SHEN; Yuqin LI; Wanning LIU; Kaisong XIANG; Hui LIU (能源环境保护)
CF4 (tetrafluoromethane), a perfluorinated compound with high thermal stability and global warming potential, poses significant challenges for the conventional catalytic decomposition route due to its robust C—F bonds and chemical inertness. Current thermal catalytic technologies, primarily using aluminum-based catalysts, have demonstrated efficient CF4 decomposition but require reaction temperatures exceeding 600 ℃, which is far beyond the maximum temperature of flue gas from actual aluminum electrolysis (140 ℃). Consequently, there is an urgent need to develop low-temperature CF4 catalytic decomposition technologies to reduce greenhouse gas emissions from the aluminum electrolysis industry. To address this challenge, researchers have proposed the strategy of coupling aluminum-based catalysts with low-temperature plasma. Notably, the hydroxyl-enriched mesoporous aluminum catalyst exhibits remarkable CF4 decomposition efficiency even at room temperature (25 ℃). The key to this breakthrough lies in the formation of hydroxyl sites on the aluminum surface. Hydroxyl-enriched mesoporous aluminum has been successfully prepared through the sol-gel method using aluminum isopropoxide as the aluminum source, which significantly enhances CF4 decomposition efficiency. Experimental results show that, under the reaction conditions of 10% CF4 concentration and 10 mL/min flow rate, the highest decomposition efficiency of CF4 can reach 95% using a mesoporous aluminum catalyst coupled with plasma. Even at a flow rate of 50 mL/min, the decomposition rates can still reach 70%. These findings underscore the potential of this new catalyst in practical applications. Compared to commercial alumina, mesoporous aluminum demonstrates superior properties. Specifically, the strong acidic sites and hydroxyl content of mesoporous aluminum are 16.2% and 118.0% higher, respectively. The surface of mesoporous aluminum contains higher densities of acidic and basic sites, with the weak basic sites being Al—OH and strong basic sites being active oxygen species such as O2−. During the CF4 decomposition reaction, the Al—OH groups on the surface of mesoporous aluminum participate in the decomposition process, transforming CF4 into carbon (C) and aluminum fluoride (AlF3). These products deposit on the catalyst surface, leading to pore blockage and a subsequent decrease in CF4 decomposition efficiency after prolonged reaction. The hydroxyl group plays a pivotal role in CF4 decomposition by serving as a proton donor and an active site. Its dual functionality as a Brønsted acid and a base enhances the overall performance of CF4 decomposition. The presence of hydroxyl groups facilitates the breakdown of CF4 and improves the catalyst's stability and longevity, making it a promising solution for reducing greenhouse gas emissions from aluminum electrolysis processes in industrial applications.